Florence Kelley’s Struggle against Child Labour: Revisiting the Obstacles - Schneider, Nina (My University, 2022)
Florence Kelley (1859–1932) was a leading American reformer and activist against child labour. As an admired national icon, most of the biographical and scholarly accounts focus on her achievements. This article, by contrast, analyses and categorises the numerous obstacles Kelley had to face in her activist life, hereto barely discussed in the Kelley literature. Drawing mainly on her private papers from the New York Public Library, her autobiography, and edited letters, it focuses on her personal experiences and helps to reconstruct the shadowy sides of her activism. Offering an unpolished historical account rather than a simple and incomplete success story, it aims to give readers a grasp of her perseverance, intelligence, and capacity to change her strategy in pursuit of her goals. Often what seemed to be an obstacle turned out to be an important crossroads on the way towards the next important step in her activist life. Overall, the article reconstructs and categorises episodes involving the lesser-known everyday obstacles she faced, but also critically revisits the way Kelley’s activism has been portrayed in the literature.
Keywords: Aktivismus; biography; Florence Kelley; Frauenrechte; movement against child labour; social activism; USA; women’s rights; ddc:970